Consenting to health record linkage: Evidence from the British household panel study - Gundi Knies; Emanuela Sala; Jonathan Burton (University of Essex, Institute for Social and Economic Research (ISER), 2011)
The British Household Panel Survey (BHPS) is the first study of its kind to have asked for permission to link to a range of administrative health records. Multivariate analysis is applied to investigate whether there is consent bias. We find that consent on the BHPS is not biased with respect to socio-economic characteristics or health; recent users of GP services are underrepresented among consenters. Whilst consent rates are lower than on previous surveys with a more medical focus, the problem of bias is less of an issue.
Keywords: I19; C83; Z00; 330; data linkage; consent; BHPS; selection bias; health inequality